Safety and efficacy of lecanemab for Alzheimer's disease: a systematic review and meta-analysis of randomized clinical trials - Qiao, Yue; Chi, Yuewei; Zhang, Qingyuan; Ma, Ying (Frontiers in Aging Neuroscience, 2023)
Objective: We performed a systematic review and meta-analysis of the cognitive effectiveness and safety of lecanemab on subjects with Alzheimer’s disease (AD). Methods: We screened the literature published before February 2023 in the Pubmed, Embase, and Web of Science, and Cochrane were searched for randomized controlled trials testing lecanemab for the treatment of cognitive decline in patients with MCI or AD, Outcomes measured were CDR–Sum of Boxes (CDR-SB), Alzheimer’s Disease Composite Score (ADCOMS), AD Assessment Scale-Cognitive Subscale (ADAS-Cog), Clinical Dementia Rating (CDR), Amyloid PET Standardized Uptake Volume Ratio (SUVr), Amyloid burden on PET, and risks for adverse events. Results: A total of 4 randomized controlled trials were included, involving 3108 AD patients (1695 lancemab group and 1413 placebo group) to synthesize evidence. Baseline characteristics of the two groups were similar in all outcomes except that ApoE 4 status and higher MMSE score were observed in the lancemab group. It is reported that lancemab was beneficial to stabilize or slow down the decrease of CDR-SB (WMD: -0.45; 95% CI: -0.64, -0.25; p <0.00001), ADCOMS (WMD: -0.05; 95% CI: -0.07, -0.03; p <0.00001),ADAS-cog (WMD: -1.11; 95% CI: -1.64, -0.57; p <0.0001), amyloid PET SUVr (WMD: -0.15; 95% CI: -0.48, 0.19; p =0.38), amyloid burden on PET (WMD: -35.44; 95% CI: -65.22, -5.67; p =0.02), adverse events (Subjects with any TEAE) (OR: 0.73; 95% CI: 0.25, 2.15; p = 0.57), ARIA-E (OR:8.95; 95% CI: 5.36, 14.95; p < 0.00001), and ARIA-H (OR:2.00; 95% CI: 1.53, 2.62; p < 0.00001) in early AD patients. Conclusions: Our findings found that lecanemab showed significant positive efficacy with respect to cognition, function, behavior in patients with early AD. Systematic review registration: PROSPERO, identifier: CRD42023393393.